Criminology of corruption: theoretical approaches - Brooks, Graham (Palgrave Macmillan, 2016)
Introduction -- Studying corruption : an interdisciplinary problem -- The extent of corruption -- Explaining corruption : differential association -- Explaining corruption : experiencing strain in the "modern" world -- Explaining corruption : drifting in and out of corruption and techniques of neutralization -- Explaining corruption : why don't we all commit acts of corruption? -- Explaining corruption : as inevitable in a "system" of conflict? -- Explaining corruption : the power to label organizations, institutions and individuals as corrupt -- Explaining corruption : a rational, calculated choice? -- Explaining corruption : a routine "business" activity? -- Reflections and conclusion